“Who Are You Really Punishing?”: Mothers’ Experiences With an Incarcerated Son - Tadros, Eman (Crime & delinquency, 2025)
The consequences of incarceration are not solely reserved for the individual incarcerated, rather the impacts of incarceration have been shown to extend to the entire family system. The parent-child relationship is multifaceted and necessitates empirical evidence that significantly honors the voices that are at the center of experience but typically silenced by the stigma and prejudice nature of incarceration. Via a phenomenological approach, mothers of incarcerated adult sons were interviewed. Five themes emerged from eight interviews: emotional impact, barriers and challenges for families, mental health services, systemic issues, and advocacy and support. Our findings inform clinical implications for mental health professionals working with the incarcerated population. We provided recommendations on how to best advocate for this population through research, clinical work, and policy.